Adab Education Management in Islamic Boarding School: A Case Study - Shafwan, Muhammad Hambal; Suprapto, Suprapto (Jurnal Pendidikan Edutama, 2025)
This research aims to discuss how to manage adab education at the TQH al-Hasyimi Tenggulun Solokuro Lamongan Islamic Boarding School. is qualitative research with a case study approach, which means this research is carried out in a natural context to understand the phenomena that occur. The methods used include various techniques to carry out in-depth interpretation of the phenomenon. The results of this research explain that adab education at the TQH al-Hasyimi Islamic boarding school uses the book "at-Tibyan fi adab Hamalah al-Qur'an" as a guide. The implementation of learning the book "al-Tibyân fî Âdâb Hamalah al-Qur'ân" at the TQH al-Hasyimi Islamic Boarding School, with a management process that includes planning, organizing, actualling and controlling, requires time is not instant and a continuous process. In practice, students are expected to be able to apply the etiquette taught in the book, such as: (1) Cleaning the Heart: Protecting the heart from despicable qualities and always trying to gain the approval of Allah SWT; (2) Polite Appearance: Ensure a neat and polite appearance when participating in learning activities; (3) Consistency of deposit times: Prioritize deposit times in the morning to repeat memorization with discipline; (4) Getting used to night Qira'ah: Performing tadarus and night prayers regularly to increase spirituality and understanding of the Qur’an.